129I in rainwater across Argentina. (July 2022) - Negri, Agustín; Arazi, Andrés; Barlasina, María Elena; Fernández Niello, Jorge; Fifield, Leslie Keith; Froehlich, Michaela B.; Martínez Heimann, Diego; Pavetich, Stefan; Tims, Steve G.; Wallner, Anton
Abstract: Concentrations of 127 I and 129 I in rainwater samples from several stations across Argentina (latitudes between 25° S and 55° S) were measured and analyzed for the assessment of distribution patterns and potential sources of 129 I in the Southern Hemisphere. Measured 129 I levels, clearly above those explainable by natural background and atmospheric nuclear weapons tests, can be understood by the injection into the Southern Hemisphere of 129 I that had been discharged from nuclear fuel reprocessing plants in the Northern Hemisphere. Graphical abstract: Image 1 Highlights: Radioactive 129 I and 127 I content measured in rain samples across Argentina. 55°S - 40°S: 129 I content as expected from natural background and atomic weapons. 40°S - 25°S: 129 I content higher by a factor ∼10 2 . Excess explained as input of 129 I-rich air masses from the Northern Hemisphere.